The running shoe prescription - Asplund, C. A.; Brown, D. L. (The Physician and Sportsmedicine, 2005)
Running-related injuries are among the most frequent reasons for primary care visits. Armed with information on the basics of foot types, gait patterns, and running shoe design, healthcare providers can perform a simple, office-based assessment that gives the best possible advice to patients regarding the fit and features of their running shoes. Patients who wear proper foot gear may well have fewer running-related injuries.